Consequences of RNA oxidation on protein synthesis rate and fidelity: implications for the pathophysiology of neuropsychiatric disorders. (4th August 2017) - Nunomura, Akihiko; Lee, Hyoung-gon; Zhu, Xiongwei; Perry, George
Abstract : Unlike DNA, oxidative damage to RNA has received little attention presumably due to the assumed transient nature of RNA. However, RNAs including mRNA can persist for several hours to days in certain tissues and are demonstrated to sustain greater oxidative damage than DNA. Because neuronal cells in the brain are continuously exposed to reactive oxygen species due to a high oxygen consumption rate, it is not surprising that neuronal RNA oxidation is observed as a common feature at an early stage in a series of neurodegenerative disorders. A recent study on a well-defined bacterial translation system has revealed that mRNA containing 8-oxo-guanosine (8-oxoGuo) has little effect on fidelity despite the anticipated miscoding. Indeed, 8-oxoGuo-containing mRNA leads to ribosomal stalling with a reduced rate of peptide-bond formation by 3–4 orders of magnitude and is subject to no-go decay, a ribosome-based mRNA surveillance mechanism. Another study demonstrates that transfer RNA oxidation catalyzed by cytochrome c (cyt c ) leads to its depurination and cross-linking, which may facilitate cyt c release from mitochondria and subsequently induce apoptosis. Even more importantly, a discovery of oxidized microRNA has been recently reported. The oxidized microRNA causes misrecognizing the target mRNAs and subsequent down-regulation in the protein synthesis. It is noteworthy that oxidative modification to RNA not only interferes with the translational machinery but also with regulatory mechanisms of noncoding RNAs that contribute toward the biological complexity of the mammalian brain. Oxidative RNA damage might be a promising therapeutic target potentially useful for an early intervention of diverse neuropsychiatric disorders.